TRANSAKSI MATA UANG DALAM PANDANGAN ISLAM - Zainal Abidin (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2010)
The trading of money in modern era is very important tocontrol and balance of global economic. Over this system,the procces of global trading are exist and more easier.Baut in other side according to Islamic concept thetrading of maney have to follow the patterns arerecommaded. This article want to explain about thepattern about Islamic concept in the money trading. Theminimal target is may be can give inspiration and spiritin money trading. The target is not impossible if we mantto do effort to do something especially in the system oftransaction, the statement of transaction, etc. To changethe all of methode in the modern/commercial system inthe money trading is imposible but create the newsystem mhich the convergent between Islamic andcommercial system in trading of money is impoosibleand be the target.